Factors Affect Purchase Intention of Retail Pharmacy in Malaysia - Hoo, Wong Chee; Huey, Janice Lau Shin; Teck, Tan Seng; Yew, Lim Kim; Fei, Goh Chin; Kowang, Tan Owee; Hee, Ong Choon (International Journal of Psychosocial Rehabilitation, 2020)
Abstract: Retail pharmacy industry in Malaysia is expanding rapidly. The growth is driven by the rising income, lifestyle changes and increased need for medicines. The strong competition in this industry had posed a threat to the survival of Malaysian pharmacy business. The study of purchase intention is important because a positive intention allows retailers to gain increased sales and revenues as purchase intention is strong predictor with consumer’s actual purchase behaviour. Consumer’s purchase intention in choosing a retail pharmacy in Malaysia can be influenced by several factors. It is observed that consumer’s purchase intention has been discussed in multiples researches in Malaysia. However, there are limited studies undertaken on consumer’s purchase in choosing a retail pharmacy in Malaysia. Therefore, this study narrowed the literature gap by ascertaining the factors influencing consumer’s purchase intention in choosing a retail pharmacy in Malaysia. Social media marketing, store environment, sales promotion, perceived value and CSR were identified as the five independent variables of this study. The objective of this study is to investigate the impact between the factors and consumer’s purchase intention in choosing a retail pharmacy in Malaysia. This study adopted multiple regression analysis (SPSS) as the major statistical method and a total of 385 subjects recruited in this study were selected conveniently through the distribution of self-administered questionnaire in Malaysia. This study reported that social media marketing, store environment, sales promotion, perceived value and CSR were found to have a significant relationship with consumer’s purchase intention in choosing retail pharmacy in Malaysia. Store environment had shown to impact the most on consumer’s purchase intention followed by perceived value.